2020
DOI: 10.1016/j.nmni.2020.100824
|View full text |Cite
|
Sign up to set email alerts
|

Uropathogenic Escherichia coli in the high vaginal swab samples of fertile and infertile women: virulence factors, O-serogroups, and phenotyping and genotyping characterization of antibiotic resistance

Abstract: Transmission of urinary tract infections into the reproductive system is unavoidable. The present research was performed to assess the distribution of virulence genes, O-serogroups and antibiotic resistance properties of uropathogenic Escherichia coli (UPEC) strains isolated from the high vaginal swab samples of fertile and infertile women. A total of 460 high vaginal swab samples were taken from fertile and infertile women. Distribution of virulence factors and serogroups and antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Ten microliters of PCR product were exposed to electrophoresis in a 2% agarose gel in 1X TBE buffer at 80 V for 30 min, stained with SYBR Green. The UVI doc gel documentation systems (Grade GB004; Jencons PLC, London, UK) were applied to analyze images (Ghorbani et al., 2016; Dehkordi et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Ten microliters of PCR product were exposed to electrophoresis in a 2% agarose gel in 1X TBE buffer at 80 V for 30 min, stained with SYBR Green. The UVI doc gel documentation systems (Grade GB004; Jencons PLC, London, UK) were applied to analyze images (Ghorbani et al., 2016; Dehkordi et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…In a study conducted by Dehkordi et al, 65 out of 406 (14.13%) swab samples were positive for E. coli. 18 When we treated these patients according to sensitivity report, patients got complete relief of symptoms and repeat culture report came out to be negative.…”
Section: Resultsmentioning
confidence: 99%
“…This is similar to the microbial changes in the vagina and cervix. Urinary and reproductive systems are closely associated with each other and infections of one system can easily transmit to another (Safarpoor Dehkordi et al, 2020). Sequencing analysis of the bacterial strains isolated from the vagina and bladder in the same woman showed that Escherichia coli, Streptococcus anginosus, L. iners, and L. crispatus were highly similar between them (Thomas- White et al, 2018).…”
Section: Discussionmentioning
confidence: 99%